Advanced analysis method of electric propulsion system for UAM vehicles - Lee, D.; Lee, K. (My University, 2021)
This article proposes an advanced analysis method of the electric propulsion system for UAM vehicles. Three modules are constructed to consider the electrical characteristics of electric devices. The motor-analysis module is developed based on the permanent magnet synchronous motor (PMSM)'s control strategies: maximum torque per ampere (MTPA), field weakening (FW), and maximum torque per voltage (MTPV). The inverter-analysis module uses the linear loss model for the power semiconductors. Based on the near-linear discharge model, the battery-analysis module was constructed to consider the voltage drop. In addition, the eVTOL aircraft sizing is performed in two cases depending on the type of analysis method for the electric propulsion system. The comparative study based on the sizing results demonstrates the necessity and the capability of the proposed analysis method for the electric propulsion system.